Diagnostic Accuracy of the Triglyceride and Glucose Index for Insulin Resistance: A Systematic Review - Adriana Sánchez-García; René Rodríguez-Gutiérrez; Leonardo Mancillas-Adame; Victoria González-Nava; Alejandro Díaz González-Colmenero; Ricardo Cesar Solis; Neri Alejandro Álvarez-Villalobos; José Gerardo González-González (International Journal of Endocrinology)
Introduction. The triglyceride and glucose (TyG) index has been described as a biochemical marker of insulin resistance (IR); however, its diagnostic accuracy remains uncertain. Objective. To summarize the evidence assessing the diagnostic accuracy of the TyG index regarding IR. Methods. A comprehensive search in MEDLINE, EMBASE, Web of Science, and Scopus was performed without any language restriction. Studies assessing the diagnostic accuracy of the TyG index against the hyperinsulinemic-euglycemic clamp (HIEC) or any other IR biochemical were assessed independently and in duplicate. Diagnostic accuracy measures (sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios) were extracted independently and in duplicate. The QUADAS-2 tool was used to assess the risk of bias of independent studies. Results. We identified 15 eligible studies with 69,922 participants and an overall quality of low to moderate. The TyG index was evaluated by HIEC and HOMA as reference tests. The highest achieved sensitivity was 96% using HIEC, and the highest specificity was of 99% using HOMA-IR, with a cutoff value of 4.68. AUC values varied from 0.59 to 0.88. Cutoff values for IR were variable between studies, limiting its comparability. Conclusion. In this systematic review, we found moderate-to-low quality evidence about the usefulness of the TyG index as a surrogate biochemical marker of IR. Due to the lack of a standardized IR definition and heterogeneity between studies, further validation and standardized cutoff values are needed to be used in clinical practice.